2008
DOI: 10.1002/cne.21800
|View full text |Cite
|
Sign up to set email alerts
|

Sensory‐dependent asymmetry for a urine‐responsive olfactory bulb glomerulus

Abstract: An unusual property of the olfactory system is that sensory input at the level of the first synapse in the olfactory bulb takes place at two mirror image glomerular maps that appear identical across the axis of symmetry. It is puzzling how two identical odor maps would contribute to sensory function. The functional units in these maps are the glomeruli, ovoid neuropil structures formed by axons from olfactory sensory neurons expressing the same olfactory receptor. Here we find that the genetically identified P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…The present results indicate that during plastic responses to chronic odorant exposure, supernumerary glomeruli are added and consolidated as the olfactory bulb matures; no glomerular elimination was seen under any experimental condition (Figure 3 and S3). This result is compatible with the idea that at least under chronic odorant exposure before, during or after glomerular formation, the olfactory bulb uses a constructivist strategy, both at the circuit and glomerular levels, to respond to increased sensory demands; however, this process did not involve an increase of total glomerular volume (Figure 2 and S4); also see [14], [39]. In summary, the present results document a new strategy for the developing olfactory bulb to engange plastic responses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present results indicate that during plastic responses to chronic odorant exposure, supernumerary glomeruli are added and consolidated as the olfactory bulb matures; no glomerular elimination was seen under any experimental condition (Figure 3 and S3). This result is compatible with the idea that at least under chronic odorant exposure before, during or after glomerular formation, the olfactory bulb uses a constructivist strategy, both at the circuit and glomerular levels, to respond to increased sensory demands; however, this process did not involve an increase of total glomerular volume (Figure 2 and S4); also see [14], [39]. In summary, the present results document a new strategy for the developing olfactory bulb to engange plastic responses.…”
Section: Discussionsupporting
confidence: 88%
“…In support of this possibility, we documented volume redistribution and topological closeness among supernumerary I7 and M72 glomeruli, as well as the local primary afferent reorganization in mice exposed chronically to cognate odorants. Complementarily or alternatively, our results can also be attributed to modified patterns of spontaneous and/or increased or reduced presynaptic and/or postsynaptic neuronal activity [12], [14], [18], [31][34], shifts in the availability of cAMP associated with OR activation [34][36], differential activation of G protein and/or adenylate cyclase [35][37] and/or changes in BDNF availability [14], [38]. All the named factors are known to greatly influence the degree of glomerular axon coalescence and arborization, and glomeruli spatial distribution and number.…”
Section: Discussionmentioning
confidence: 72%
“…Given the well known effect of OR expression on OSN axon targeting (Mombaerts, 2006), if loss of odor selectivity were due to dysregulation of OR gene expression resulting in expression of multiple ORs per OSN, we would expect changes in glomerular formation in the olfactory bulb. In addition, because axon targeting is affected by OSN activity (Kerr and Belluscio, 2006,Oliva, et al, 2008,Zou, et al, 2004), it is possible that loss of OSN selectivity in the elderly would affect glomerular structure. Indeed, studies in mice show that glomerular axon targeting by OSNs expressing the P2 olfactory receptor is increasingly diffuse with age with a subset of axons partially innervating glomeruli in elderly mice (Costanzo and Kobayashi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an MRI study using three-dimensional voxel-based analysis found asymmetry in the size of both hemispheres in the sensory cortical and subcortical regions of mice of the same age (Spring et al, 2010). In the case of olfactory processing, asymmetrical activation patterns of glomeruli in both olfactory bulbs were reportedly observed during odorant stimulation (Xu et al, 2000;Kida et al, 2002); this finding was ascertained at the level of the individual glomerulus by genetic tracing techniques (Oliva et al, 2008). Furthermore, genetic tracing techniques were also used to verify the characteristics of the gustatory system, in which sweet and bitter taste receptor cells transform to the insular cortex of both hemispheres; most of the clusters of labeled neurons appeared were located on both sides, but asymmetrically, in the insular cortex of the mouse brain (Sugita and Shiba, 2005).…”
Section: Discussionmentioning
confidence: 96%